An efficient hybrid system using a thermionic generator to harvest waste heat from a reforming molten carbonate fuel cell. (1st August 2016) - Huang, Chuankun; Pan, Yuzhuo; Wang, Yuan; Su, Guozhen; Chen, Jincan
Highlights: A new hybrid system includes a molten carbonate fuel cell and a thermionic generator. Losses in reforming, electrochemical, and heat transfer processes are considered. Performances of the hybrid system and the single MCFC are compared. Optimal regions of some key parameters including two loads are determined. Advantages of the present system over other MCFC-based hybrid systems are shown. Abstract: A new hybrid system consisting of an internal reforming molten carbonate fuel cell (IR-MCFC) and a vacuum thermionic generator (TIG) is constructed. By considering the main irreversible losses in two subsystems and the coupling process, general expressions for the power output and efficiency of the hybrid system are derived. The performance characteristics of the hybrid system are revealed, and the optimal regions, including the power output, efficiency, and load resistances, are determined. It is found that the maximum power output density of the IR-MCFC/TIG system increases by 22% compared to that of a single MCFC, and among the IR-MCFC- and MCFC-based hybrid systems reported in the literature, the present hybrid system can most efficiently harvest the waste heat from the MCFC.